Küstenbilder - Bilder der Küste. Interdisziplinäre Ansichten, Ansätze und Konzepte - Döring, Martin (Hamburg University Press, 2006)
The reference point for this publication is the concept of the "coastal image" which is represented from different professional perspectives by their representatives. The aim of the volume is not a synthesis of different positions, but rather to identify divergences and convergences that could trigger the technical discussion. The pluralism of perspectives on the "coastal image" in the individual scientific disciplines and practice areas presented in this volume is therefore deliberate and represents interdisciplinary views, approaches and concepts for accessing the "coastal image".